If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + 8) + -1(5 + 3y) = 11 Reorder the terms: (8 + 4y) + -1(5 + 3y) = 11 Remove parenthesis around (8 + 4y) 8 + 4y + -1(5 + 3y) = 11 8 + 4y + (5 * -1 + 3y * -1) = 11 8 + 4y + (-5 + -3y) = 11 Reorder the terms: 8 + -5 + 4y + -3y = 11 Combine like terms: 8 + -5 = 3 3 + 4y + -3y = 11 Combine like terms: 4y + -3y = 1y 3 + 1y = 11 Solving 3 + 1y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1y = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 1y = 11 + -3 1y = 11 + -3 Combine like terms: 11 + -3 = 8 1y = 8 Divide each side by '1'. y = 8 Simplifying y = 8
| -7(x+2)-7=-14+7(x+4) | | ln(y-1)-ln(2)=xln(x) | | 6t=8t-6 | | 3x+2(5x-4)=7 | | 6m=5m-6 | | 48x^2-19x-60=0 | | p+27+p-7=6 | | (x-5)-4=3(x-3) | | 8p-2=-10+10p | | -10c-1=-3c-7-8c | | A^2x^3-10a^2x^2+24a^2x=0 | | 13+h-14+h=29 | | 17=5k-7+7k | | 10z-9=-9z+10 | | 2a*6c=12ac | | 2a*6c= | | -5n=-3n-8 | | 7x+3+2x=5+10x-10 | | 6y+3(y-9)=5(y+1)-3 | | -92+9x=103-6x | | 2y-9=4y+9 | | 5(x+3)=7x-21 | | q+10=-9q | | N^2+3n+c=0 | | 6(41-21)-6(20-3)= | | 14+h-14+h=30 | | 6q-8=5q | | 9k+8=K+14 | | 12ac-7c=5a | | 8w+5=4 | | -7-9j=-10j | | 12ac-7c= |